Incidence and Damage Estimation of Brinjal Shoot and Fruit Borer in Five Different Brinjal Varieties - Ara, S; Nahar, N; Rahman, M (Progressive Agriculture, 2014)
An experiment was conducted to observe the incidence of brinjal shoot and fruit borer, Leucinodes orbonalis Guen. and to estimate their damages in five different brinjal varieties (viz. Laffa, Dohazari, Uttara, Islampuri and Amjuri) in the Plant Pathology Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from January to March, 2007. Peak period of brinjal shoot and fruit borer infestation was observed in March in all the five varieties. Maximum number of population (5.0 per plant) was recorded in Amjuri variety in first week of March whereas minimum number of population (0.33 per plant) was observed in Dohazari variety in the third week of March. No infestation was found from 3rd week of January to 3rd week of February in all the five tested brinjal varieties. Brinjal shoot and fruit borer caused damages to shoots and fruits of brinjal plant and it was found that all the tested brinjal varieties are susceptible to the borer. In case of all tested varieties, mean number of damaged shoots and fruits per plant differed significantly at different sampling times. Among the five varieties Amjuri was heavily infested with the highest infestation of shoot and fruit. In this variety, mean number of damaged fruit per plant was 2.11, 1.67 and 1.87 at first, second and third week of March, respectively. In Islampuri variety, shoot infestation was found only in the 3rdweek of March. DOI: http://dx.doi.org/10.3329/pa.v18i2.18162 Progress. Agric. 18(2): 75 - 80, 2007